Proteomic profiling reveals important regulators of photosynthate accumulation in wheat leaves during grain development - Wanting Li; Xiangrui Liu; Zeyu Shi; Yifei Wang; Wenqiang Tang; Huimin Ren; Baowen Zhang (BMC Plant Biology)
Abstract Background Wheat yield potential is intrinsically linked to the efficiency of photosynthetic carbon fixation and subsequent allocation to developing grains. While leaves are recognized as the dominant source of photosynthate, the molecular drivers governing temporal shifts in source tissue function during grain filling remain unresolved, leaving a critical gap in knowledge about the proteomic reprogramming underlying natural developmental transitions. Addressing this gap could reveal novel targets for enhancing carbohydrate partitioning efficiency and improving agronomic yield in wheat. Results This study presents a comprehensive temporal proteomic analysis of wheat source tissues (the flag leaf and -2nd leaf), from the initiation of the grain filling stage to the termination of source-to-sink transport (10–40 days after anthesis, DAA), using a data-independent acquisition (DIA)-based proteomics approach. Weighted gene co-expression network analysis (WGCNA) identified significant enrichment of photosynthesis-related proteins, carbohydrate metabolic enzymes, and cytokinin metabolic enzymes during the early grain filling stage (10–15 DAA). Integrated co-expression clustering and multiple expectation maximizations for motif elicitation (MEME) analysis revealed strong enrichment of Dof (DNA binding with one finger) transcription factor binding cis-elements in the promoters of carbohydrate synthesis-related genes. Additionally, through haplotype-phenotype association studies, we identified favorable Dof family haplotypes that were significantly associated with increased thousand-grain weight (TGW) and enhanced leaf chlorophyll content. Conclusions Our findings not only provided a systematic characterization of proteome dynamics in wheat source tissues during the grain filling stage, but also revealed several key regulatory proteins that may control carbohydrate accumulation in source tissues, offering potential new targets for breeding strategies aimed at improving wheat yield.